Preliminary evaluation of the antiglycoxidant activity of verapamil using various in vitro and in silico biochemical/biophysical methods - Nesterowicz, Miłosz; Lauko, Kamil Klaudiusz; Dańkowska, Karolina; Trocka, Daria; Żendzian-Piotrowska, Małgorzata; Ładny, Jerzy Robert; Zalewska, Anna; Maciejczyk, Mateusz (Frontiers in Pharmacology, 2023)
Introduction: Glycoxidative stress is essential for linking glucose disturbances and cardiovascular diseases. Unfortunately, contemporary antidiabetic drugs do not have an antiglycative effect but only lower blood glucose levels. Therefore, there is an intense search for substances that could inhibit protein glycation and prevent diabetic complications. A potential antioxidant activity has been demonstrated with verapamil, a phenylalkylamine derivative belonging to selective calcium channel blockers. Verapamil has a well-established position in cardiology due to its wide range of indications and good safety profile. Nevertheless, the antidiabetic activity of verapamil is still unclear. We are the first to comprehensively evaluate the verapamil's effect on protein glycoxidation using various in vitro and in silico models.Methods: Bovine serum albumin (BSA) was used to assess the rate of glycoxidation inhibition by verapamil. As glycating factors, sugars (glucose, fructose, and ribose) and aldehyde (glyoxal) were used. Chloramine T was used as an oxidizing agent. Aminoguanidine (protein glycation inhibitor) and Trolox (antioxidant) were used as control substances. The biomarkers of oxidation (total thiols, protein carbonyls, advanced oxidation protein products), glycation (Amadori products, β-amyloid, advanced glycation end products [AGEs]), and glycoxidation (tryptophan, kynurenine, N-formylkynurenine, dityrosine) were evaluated using colorimetric and fluorimetric methods. The mechanism of antiglycative activity of verapamil was assessed using in silico docking to study its interaction with BSA, glycosidases, and seventeen AGE pathway proteins.In all in vitro models, biomarkers of protein glycation, oxidation, and glycoxidation were significantly ameliorated under the influence of verapamil. The glycoxidation inhibition rate by verapamil is comparable to that of potent antiglycating agents and antioxidants. The molecular docking simulations showed that verapamil bound preferentially to amino acids prone to glycoxidative damage out of an α-glucosidase's active center. Among all AGE pathway proteins, verapamil was best docked with the Janus kinase 2 (JAK2) and nuclear factor-κB (NF-κB).The results of our study confirm the antiglycoxidant properties of verapamil. The drug's action is comparable to recognized substances protecting against oxidative and glycation modifications. Verapamil may be particularly helpful in patients with cardiovascular disease and concomitant diabetes. Studies in animal models and humans are needed to confirm verapamil's antiglycative/antidiabetic activity.